Contribution of integrated forest-farm system on household food security in the mid-hills of Nepal: assessment with EnLiFT model. (15th May 2019) - Cedamon, E. D.; Nuberg, I.; Mulia, R.; Lusiana, B.; Subedi, Y. R.; Shrestha, K. K.
ABSTRACT: About half of the households in the mid-hills of Nepal are severely food insecure, and the development of agriculture and forestry sectors could hold keys to reduce food insecurity and achieve other sustainable development goals. This paper presents results from a bio-economic model, Enhancing Livelihood from Improved Forest Management in Nepal (EnLiFT), that estimates a Food Security Index (FSI) across six household types in rural Nepal simulating selected agroforestry livelihood interventions. The FSI is calculated as the ratio between household expenditure capacity and household poverty threshold based on the national per capita poverty threshold. Market-oriented timber production shows strong potential to increase food security across all household types with greater benefits accruing to land-rich households. For land-poor households, remittances from household members working abroad remains the strongest route to their food security despite the underutilisation of agricultural land due to adult male labour outmigration. A drawback of market-oriented timber production is the long-term nature of timber production. As EnLiFT assumes that timber can only be harvested from Year 9, complimentary livelihood strategies are required to address food insecurity in the short term. Complimentary agroforestry interventions with the strongest potential to improve food security include combined high-yielding fodder production and commercial goat production, and production of non-timber forest products. Commercial vegetable production does not improve food security because of the high input costs. Currently, farmers in Nepal cannot yet fully obtain the financial benefits of agroforestry due to the complex and unsupportive forestry regulations surrounding harvesting and marketing of planted trees. While land-poor households are seen to rely on foreign remittances for food security, it is argued that policies encouraging use of remittances to promote agroforestry businesses is needed.